Senam Diabetes terhadap Perubahan Kadar Gula Darah Sewaktu pada Komunitas Diabetes Mellitus - Yani, Sri; Bachtiar, Faradina (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Diabetes exercise is believed to have benefits in controlling blood sugar levels and blood pressure for peoplewith Diabetes Mellitus (DM). This study aims to examine diabetes exercise in DM sufferers to changes in thelevel of postprandial blood sugar. This research method used retrospective observational analysis which wascarried out based on records of blood sugar tests during June-December 2019 in the diabetes community whoreceived diabetes exercise once a week. The normality test used the Saphiro-Wilk test and bivariate analysisusing the Friedman-Test test. Data analysis used IBM SPSS Statistics 22. Based on the results of the study, itwas found that the total participants in the community group who routinely did diabetes exercises were 61people. After screening based on the criteria set by the researcher, data were obtained from 24 respondents.